2003
DOI: 10.1128/iai.71.7.3837-3843.2003
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Properties of HpaA and Omp18, Two Outer Membrane Proteins ofHelicobacter pylori

Abstract: Outer membrane proteins (OMPs) are incorporated into the outer plasma membrane of Helicobacter pylori and are important for, e.g., ion transport, adherence, structural and osmotic stability, and bacterial virulence but may also be antigenic due to their surface exposure. Previous proteome-based approaches with H. pylori lysates determined a strong serological reaction towards two H. pylori OMPs, HpaA (TIGR HP0797) and Omp18 (TIGR HP1125). PCR was used to detect DNA encoding the two proteins, and a positive sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 33 publications
1
43
1
1
Order By: Relevance
“…Sharma et al demonstrated that IL-8 production by gastric epithelial cells is not solely dependent on the presence of CagA and VacA, but other bacterial constituents are clearly essential (53). H. pylori has a complex structure and harbors several potential immunostimulatory PAMPs (LPS, DNA, and flagellin), as well as outer membrane proteins like HpaA and Omp18 (61). Therefore, it would be surprising if the innate immune response were stringently controlled by the presence or absence of cag PAI and VacA.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al demonstrated that IL-8 production by gastric epithelial cells is not solely dependent on the presence of CagA and VacA, but other bacterial constituents are clearly essential (53). H. pylori has a complex structure and harbors several potential immunostimulatory PAMPs (LPS, DNA, and flagellin), as well as outer membrane proteins like HpaA and Omp18 (61). Therefore, it would be surprising if the innate immune response were stringently controlled by the presence or absence of cag PAI and VacA.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells have been observed to extend their lamina podia across an intact epithelium via a paracellular pathway and hence can sample luminal antigen across an intact epithelium. Once dendritic cells bind H. pylori or H. pylori antigens, they can induce an immune response with features of both a Th1 and Th2 response with increased production of both IL-12 (a key cytokine in shifting the immune response from a Th0 to a Th1 response) and IL-10 (a classic Th2 cytokine) [88,89].…”
Section: Proposed Theories Molecular Mimicrymentioning
confidence: 99%
“…25,27 We first nonintegrin (DC-SIGN) is the DC surface receptor that binds H. pylori glycans 11,12 and that H. pylori stimulates DCs predominantly through a Toll-like receptor (TLR)-dependent signaling cascade. 13 H. pylori-pulsed DCs (HP-DC) promote a type 1 helper T cell (Th1) response [14][15][16][17][18][19][20] and, as shown more recently, an interleukin (IL)-17-producing helper T cell (Th17) response. 21 Several studies have suggested the immunoregulatory effects of H. pylori on DCs.…”
Section: Helicobacter Pylori Directs Tolerogenic Programming Of Dendrmentioning
confidence: 99%